DETERMINATION OF CHARACTERISTIC OPTIC WAVELENGTHS FOR RELIABLE CONTROL OF SUBSTANCE COMPOSITION - Kukharchuk, Vasyl; Bogachuk, Volodymyr; Graniak, Valeriy (Scientific Works of Vinnytsia National Technical University, 2015)
The given paper suggests the method of selection of information and reference optic wave for measurement of substance composition applying optic methods, future trends concerning the usage of various optical ranges for express-measurement of substance composition are considered. REFERENCES 1. Богачук В. В. Методи та засоби вимірювального контролю порошкоподібних матеріалів: моногр. / В. В. Богачук, Б. І. Мокін – Вінниця: УНІВЕРСУМ-Вінниця, 2008. – 141 с. – ISBN-966-641-245-6 2. Берлинер М. А. Измерение влажности. – Изд. 2-е, переработанное и дополненное. / М. А. Берлинер – М.: Энергия, 1973. – 420 с. 3. Кухарчук В. В. Аналіз методів неруйнівного контролю вологості гетерогенних дисперсних діелектриків / В. В. Кухарчук, В. В. Богачук, І. К. Говор, В. Ф. Граняк // Вісник ВПІ. – 2009, №5. – С. 7 – 14. 4. Матвеев А. Н. Атомная физика: учебное пособие для студентов вузов / А. Н. Матвеев – М.: Высшая школа, 1989. – 439 с. 5. Молекулярные спектры [Электронный ресурс]: Словари и энциклопедии на Академике / Режим доступу: http://dic.academic.ru/dic.nsf/enc_physics/1747/%D0%9C%D0%9E%D0%9B%D0%95%D0%9A%D0%A3%D0%9B %D0%AF%D0%A0%D0%9D%D0%AB%D0%95. 6. Сивухин Д. В. Общий курс физики: учебное пособие для вузов. В 5 т. Т. VI. Оптика / Д. В. Сивухин – М.: Физматлит, 2005. – 795 с. 7. Лансберг Г. С. Оптика: учебное пособие для вузов. / Г. С. Лансберг – М.: Физматлит, 2003 г. – 848 с.